Navigating the complexities: South Africa’s journey in collecting data for international reading literacy assessments - Roux, Karen (Frontiers in Education, 2025)
Data collection for international large-scale assessments, such as the Progress in International Reading Literacy Study (PIRLS), is a multifaceted process that demands meticulous planning, coordination, and execution to ensure accuracy and comparability across participating countries. This paper explores South Africa’s endeavours in collecting PIRLS data over the last two cycles (2016 and 2021). South Africa has faced unique challenges and opportunities in its quest to provide reliable data on reading literacy among primary school students. The data collection involves a collaborative effort between national education departments, schools, and international coordinating bodies. Key steps include sampling, instrument translation and adaptation, field staff training, data collection, and quality assurance measures. Investigating South Africa’s PIRLS data collection efforts highlights significant advancements in administrative capacity, stakeholder engagement, and methodological rigour. However, it also reveals persistent issues such as resource constraints, infrastructural disparities, and the need for continuous professional development. This paper underscores the importance of sustained investment in educational research infrastructure and international collaboration to enhance the quality of data collection processes. Ultimately, South Africa’s experiences offer valuable insights for other nations striving to improve their participation in international assessments, contributing to a more comprehensive understanding of global educational outcomes and driving evidence-based policy decisions.